2015
DOI: 10.1177/1039856215584525
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of amphetamine type stimulant-related admissions in Albany, Western Australia: 2008–2013

Abstract: The number of recognised ATS-related presentations is increasing at Albany Health Campus. A broad age range and comparatively high proportion of women were hospitalised. These patients have complex needs and many had multiple ATS-related admissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…The prevalence of psychosis identified here (34.4%) is similar, albeit a little higher, to findings reported in the literature of 27% and 26% and this could be due to our study examining patients referred to the EDMHT only. 7,11 Our study reports relatively low rates of aggression in ATS ED presentations (12.2%), at least in comparison to some of the literature. The rates of ATS user aggression in Australian EDs reported in the literature ranges from 8.3% in an ED in Perth to 65.4% in a Melbourne ED.…”
Section: Discussionsupporting
confidence: 46%
“…The prevalence of psychosis identified here (34.4%) is similar, albeit a little higher, to findings reported in the literature of 27% and 26% and this could be due to our study examining patients referred to the EDMHT only. 7,11 Our study reports relatively low rates of aggression in ATS ED presentations (12.2%), at least in comparison to some of the literature. The rates of ATS user aggression in Australian EDs reported in the literature ranges from 8.3% in an ED in Perth to 65.4% in a Melbourne ED.…”
Section: Discussionsupporting
confidence: 46%
“…Males were two to three times more likely than females to have an ATS-related presentation or admission, higher than that found in other studies. 7 The Pilbara region has recently experienced an influx of predominantly males working in the mining industry. 8 Anecdotal and media reports have suggested ATS use is high among Fly In/Fly Out (FIFO) workers.…”
Section: Discussionmentioning
confidence: 99%
“…6 In rural WA, studies have identified a sharp rise in the number of ATS-related admissions from 2011 onwards. 7 However, no studies have been undertaken in remote regions such as the Pilbara in northern WA. The region has a large population of fly-in-fly-out workers, a higher male population and a larger Aboriginal population, all factors associated with methamphetamine use.…”
Section: Psychiatrymentioning
confidence: 99%
“…Some important differences between the study's inpatient and outpatient participants were noted. Methamphetamine (ice) use in outpatients was found to be almost twice more prevalent than that for inpatients, reflecting recent research revealing increases in the use of ice in regional Australian communities (Ridley & Coleman ). Unlike the inpatients, who generally came from across the state, including metropolitan areas, the outpatients were geographically located in nearby smaller regional centres.…”
Section: Discussionmentioning
confidence: 99%